Cultural Imperialism and the Indo-English Novel : Genre and Ideology in R. K. Narayan, Anita Desai, Kamala Markandaya, and Salman Rushdie - Afzal-Khan, Fawzia (Book collections on Project MUSE., 1993)
Cultural Imperialism and the Indo-English Novel focuses on the novels of R.K. Narayan, Anita Desai, Kamala Markandaya, and Salman Rushdie and explores the tension in these novels between ideology and the generic fictive strategies that shape ideology or are shaped by it. Fawzia Afzal-Khan raises the important question of how much the usage of certain ideological strategies actually helps the ex-colonized writer deal effectively with postcolonial and postindependence trauma and whether or not the choice of a particular genre or mode employed by a writer presupposes the extent to which that writer will be successful in challenging the ideological strategies of "containment" perpetuated by most Western "orientalist" texts and writers. She argues that the formal or generic choices of the four writers studied here reveal that they are using genre as an ideological "strategy of liberation" to help free their peoples and cultures from the hegemonic strategies of "containment" imposed upon them. She concludes that the works studied here constitute an ideological rebuttal of Western writers' denigrating "containment" of non-Western cultures. She also notes that self-criticism, as implied in Rushdie's works, is not be confused with self-hatred, a theme found in Naipaul's work